I tried solving this problem myself but I have no clue where I went wrong.

This is the problem:

\(-5(3x-4)=-29+8x\)

Guest Oct 12, 2018

#1**+1 **

Its -5(3x) -(-5)4=-29 +8x <=> -15x +20 = -29 + 8x <=> 20 + 29 = 8x + 15x <=> 49 = 23x <=> x=49/23

So x=49/23 is the answer!

I hope I helped you!

Dimitristhym Oct 12, 2018

#1**+1 **

Best Answer

Its -5(3x) -(-5)4=-29 +8x <=> -15x +20 = -29 + 8x <=> 20 + 29 = 8x + 15x <=> 49 = 23x <=> x=49/23

So x=49/23 is the answer!

I hope I helped you!

Dimitristhym Oct 12, 2018